2004
DOI: 10.1152/ajplung.00174.2003
|View full text |Cite
|
Sign up to set email alerts
|

Accessory cell function of airway epithelial cells

Abstract: Oei, Erwin, Thomas Kalb, Prarthana Beuria, Matthieu Allez, Atsushi Nakazawa, Miyuki Azuma, Michael Timony, Zanetta Stuart, Houchu Chen, and Kirk Sperber. Accessory cell function of airway epithelial cells.We previously demonstrated that airway epithelial cells (AECs) have many features of accessory cells, including expression of class II molecules CD80 and CD86 and functional Fcγ receptors. We have extended these studies to show that freshly isolated AECs have mRNA for cathepsins S, V, and H [proteases importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
44
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 49 publications
1
44
0
Order By: Relevance
“…In contrast, a study by Cunningham et al (9), which also used isolated primary human Type II cells but included nonspecific Ab controls, found no CD80 or CD86 expressed on human Type II cells by flow cytometry. Other studies reporting the expression of CD80 and/or CD86 on Type II cells did not use primary isolates of Type II cells, but rather used the carcinoma-derived A549 cell line (30,31), which is sometimes used as a Type II-like cell line but is not truly representative of Type II cells of the alveolar space (32). Other reports used cultures of respiratory epithelial cells that may contain Type II cells, but also likely includes other epithelial cells that may confound their results (31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, a study by Cunningham et al (9), which also used isolated primary human Type II cells but included nonspecific Ab controls, found no CD80 or CD86 expressed on human Type II cells by flow cytometry. Other studies reporting the expression of CD80 and/or CD86 on Type II cells did not use primary isolates of Type II cells, but rather used the carcinoma-derived A549 cell line (30,31), which is sometimes used as a Type II-like cell line but is not truly representative of Type II cells of the alveolar space (32). Other reports used cultures of respiratory epithelial cells that may contain Type II cells, but also likely includes other epithelial cells that may confound their results (31).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies reporting the expression of CD80 and/or CD86 on Type II cells did not use primary isolates of Type II cells, but rather used the carcinoma-derived A549 cell line (30,31), which is sometimes used as a Type II-like cell line but is not truly representative of Type II cells of the alveolar space (32). Other reports used cultures of respiratory epithelial cells that may contain Type II cells, but also likely includes other epithelial cells that may confound their results (31). Thus, it is important to consider these issues when comparing our studies with those referenced above.…”
Section: Discussionmentioning
confidence: 99%
“…predominant expression in antigenpresenting cells; however, more recent work has demonstrated expression of CTSS in airway epithelial cells (24,25,32). Given the prevalence of CTSS in the lungs of children with CF, we investigated whether pulmonary epithelial cells represent a possible source of CTSS in the CF lung.…”
Section: Original Articlementioning
confidence: 98%
“…A range of epithelial dysfunctions have been implicated in the pathogenesis of CF lung disease, which are ultimately consequences of mutations in the CF transmembrane conductance regulator (CFTR) gene. Given that epithelial cells have been reported to express CTSS (21,24,25), we investigated the hypothesis that CF airway epithelial cells contribute to the protease burden of the CF lung by releasing increased levels of CTSS compared with non-CF control cells, and explore the mechanism responsible for our observations. Some of the results of these studies have been previously reported in the form of abstracts (26,27).…”
mentioning
confidence: 99%
“…Therefore, its localisation in the lung may pinpoint to an important function for cathepsin S. Thus, cathepsin S is also expressed in antigen-presenting cells (APC), such as macrophages and dendritic cells, and in MHC Class II cells, and could mediate CD4 + T-cell mediated immune responses. In addition, it is expressed in non-professional APCs, such as epithelial cells (12)(13)(14). Such distribution strongly suggests a role for cathepsin S in immune and inflammatory processes such that provoked by ozone exposure.…”
Section: Role Of Cathepsin S In Ozone-induced Airway Hyperresponsivenmentioning
confidence: 99%